The Effect of Demonstration Method on Problem Solving Ability of Early Childhood in Science Learning - Delviana, Dela (Universitas Islam Negeri Kiai Haji Achmad Siddiq Jember, 2022)
This research is motivated by the case has not developed the ability of early childhood problem solving, one of which occurred in a group in a kindergarten in Bandung. This is shown when the teacher asks students to perform and imitate a simple experiment in science learning, the average student directly asks for help to the teacher and does not try to think to solve the problem he faces. Therefore, the researchers tested the demonstration method in science learning on the ability of early childhood problem solving.The purpose of this study to determine: 1) the ability of problem solving in science learning by using the demonstration method. 2) the ability of problem solving in science learning by using exploration methods. 3) differences in problem solving skills in science learning between using demonstration methods by using environmental exploration methods in early childhood. This study uses a quantitative approach with quasi-experimental method, with the subject of this study consists of two classes of experimental class amounted to 12 students and control class amounted to 12 students. Data collection techniques using observation sheets and documentation. Based on the results of data analysis showed that the average value (mean) of experimental class using the demonstration method is 25.75, while the average value (mean) of control class using environmental exploration method is 25.17. In other words, the average value of the experimental class is greater than the average value of the control class. So it can be concluded that Ha is accepted and Ho is rejected, which means Ha : ?_a ?_b: there is a difference in the ability of problem solving in science learning between those who use the demonstration method and those who use the method of environmental exploration in early childhood. Abstrak Penelitian ini dilatarbelakangi oleh kasus belum berkembangnya kemampuan problem solving anak usia dini yang salah satunya terjadi pada sebuah kelompok di suatu taman kanak-kanak di Kota Bandung. Hal ini ditunjukkan ketika guru meminta siswa untuk melakukan dan menirukan sebuah percobaan sederhana pada pembelajaran sains, rata-rata siswa langsung meminta bantuan kepada guru dan tidak berusaha berpikir untuk memecahkan masalah yang dihadapinya. Oleh sebab itu, peneliti menguji cobakan metode demonstrasi pada pembelajaran sains terhadap kemampuan problem solving anak usia dini.Tujuan penelitian ini untuk mengetahui: 1) Kemampuan problem solving pada pembelajaran sains dengan menggunakan metode demonstrasi. 2) Kemampuan problem solving pada pembelajaran sains dengan menggunakan metode eksplorasi. 3) Perbedaan kemampuan problem solving pada pembelajaran sains antara yang menggunakan metode demonstrasi dengan menggunakan metode eksplorasi lingkungan pada anak usia dini. Penelitian ini menggunakan pendekatan kuantitatif dengan metode kuasi eksperimen, dengan subjek penelitian ini terdiri dari dua kelas yakni kelas eksperimen berjumlah 12 siswa dan kelas kontrol berjumlah 12 siswa. Teknik pengumpulan data menggunakan lembar observasi dan dokumentasi. Berdasarkan hasil analisis data menunjukkan bahwa nilai rata-rata (mean) kelas eksperimen dengan menggunakan metode demonstrasi yaitu 25,75, sedangkan nilai rata-rata (mean) kelas kontrol yang menggunakan metode eksplorasi lingkungan yaitu 25,17. Dengan kata lain, nilai rata-rata kelas eksperimen lebih besar dari pada nilai rata-rata kelas kontrol. Sehingga dapat disimpulkan bahwa Ha diterima dan Ho ditolak yang berarti Ha : : Terdapat perbedaan kemampuan problem solving pada pembelajaran sains antara yang menggunakan metode demonstrasi dengan yang menggunakan metode eksplorasi lingkungan pada anak usia dini.